P111 Developmental pharmacogenetics of CYP2D6 in Chinese children: loratadine as a probe drug. Issue 6 (17th May 2019) - Li, Q; Y-E, Wu; Wang, K; Shi, H-Y; Zhou, Y; Kan, M; Zheng, Y; Hao, G-X; Yang, X-M; Yang, Y-L; L-Q, Su; Wang, X-L; et al.
Abstract : Background: Although the understanding of CYP2D6 developmental pharmacogenetics in children has made great progress, the current findings are mainly focused on Caucasian children. Given the clear ethnicity difference of CYP2D6 pharmacogenetic profile, there are still unmet needs in understanding developmental pharmacogenetics in inter-ethnic population. We sought to use loratadine as a probe drug to evaluate the effects of ontogeny and pharmacogenetics on the developmental pattern of CYP2D6 in Chinese paediatric patients. Methods: Chinese children receiving loratadine treatment were enrolled in the present study. The metabolic ratio (MR) of loratadine converted to desloratadine [desloratadine concentrations/loratadine concentrations] of trough concentrations samples at steady-state condition was used as a surrogate of CYP2D6 activity. Loratadine and desloratadine were determined by LC/MS/MS method and variants of CYP2D6 were genotyped. Results: A total of 40 patients were available for final analysis. The mean age was 4.6 (range 0.5–9.0) years and the mean weight was 19.9 (range 9.0- 42.0) kg. The MR was significantly higher in homozygous wild-type subjects compared with CYP2D6*10 subjects (16.94±14.12 versus 9.37±7.54, p = 0.028). Weight was also found to be significantly corrected with MR (p = 0.030). Conclusions: The developmental pharmacogenetics of CYP2D6 in Chinese children was evaluated using loratadine as a probe drug. Weight and CYP2D6 genotype showed independently significant impacts on MR. Disclosure(s): Nothing to disclose.